2003
DOI: 10.1002/j.2164-490x.2003.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Empathy in the Therapeutic Alliance

Abstract: In this investigation of the construct of empathy, the authors report that the literature reflects strong evidence that empathy is an essential component of the therapeutic alliance across theories and that empathy is necessary in the counseling process. The concept of empathy continues to be a central component of new forms of counseling and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 25 publications
1
43
0
3
Order By: Relevance
“…Consequently the review only partially represents the literature that has documented the therapeutic relationship, or therapeutic/working alliance, the full extent of which was beyond the scope of this review. There are existing reviews and metaanalyses that have shown that a weak therapeutic alliance is associated with attachment avoidance and attachment anxiety (Bernecker, Levy & Elison, 2014), while a strong therapeutic alliance is associated with a secure attachment style (Diener, Hilsenroth & Weinberger, 2009;Smith, Mfseti & Golding, 2010), motivation, treatment readiness, positive treatment experiences (Meier, Barrowclough & Donmall, 2005), and therapists' empathy (Feller & Cottone 2003), all of which are consistent with the findings of this review (Korfmacher et al, 1998;Lecomte et al, 2012;Simpson et al, 2009). …”
Section: General Limitationsmentioning
confidence: 99%
“…Consequently the review only partially represents the literature that has documented the therapeutic relationship, or therapeutic/working alliance, the full extent of which was beyond the scope of this review. There are existing reviews and metaanalyses that have shown that a weak therapeutic alliance is associated with attachment avoidance and attachment anxiety (Bernecker, Levy & Elison, 2014), while a strong therapeutic alliance is associated with a secure attachment style (Diener, Hilsenroth & Weinberger, 2009;Smith, Mfseti & Golding, 2010), motivation, treatment readiness, positive treatment experiences (Meier, Barrowclough & Donmall, 2005), and therapists' empathy (Feller & Cottone 2003), all of which are consistent with the findings of this review (Korfmacher et al, 1998;Lecomte et al, 2012;Simpson et al, 2009). …”
Section: General Limitationsmentioning
confidence: 99%
“…Counselor empathy is often described as a component of therapeutic alliance (Anderson et al, 2009; Baldwin, Wampold & Imel, 2007;Horvath, De Re, Flückiger & Symonds, 2011) and even a necessary ingredient (Boardman, Catley, Grobe, Little, & Ahluwalia, 2006; Feller & Cottone, 2003; Hoaas, Lindholm, Berge, & Hagen, 2011; Meissner, 1996; Rogers, 1959). Baldwin et al (2007) have demonstrated that the robust relationship between therapeutic alliance and client outcomes is driven by therapist, and not client, variability in the alliance construct.…”
mentioning
confidence: 99%
“…The success of nurses administering the interventions was reported in the various included studies (Penckofer et al, 2012;Piette et al, 2011;Rungreangkulkij et al, 2011). In psychosocial interventions, the therapeutic alliance that a therapist has with the individual is one of the pivotal factors in Page 26 of 53 A c c e p t e d M a n u s c r i p t 26 determining a successful treatment (Feller & Cottone., 2003). This important bond formed between the therapist and client helps the individual work towards agreed upon goals and/or tasks (Del Re, Flückiger, Horvath, Symonds, & Wampold, 2012).…”
Section: Page 25 Of 53mentioning
confidence: 99%